2008
DOI: 10.1002/term.109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of holding time, temperature and different parenteral solutions on viability and functionality of adult bone marrow-derived mesenchymal stem cells before transplantation

Abstract: Mesenchymal stem cells (MSCs) have the ability to proliferate and differentiate into various lineages, given the appropriate microenvironment, thus making MSCs promising candidates for cell transplantation. For clinical applications, MSCs need to be stored in optimal conditions so that they may be transported and made available as an off-the-shelf product for companies to market. Freshly harvested and cultured or frozen-thawed bone marrow-derived MSCs were prepared for cell transplantation. Both freshly cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 20 publications
(17 reference statements)
7
63
2
Order By: Relevance
“…On the other hand, our results were in contradictory to certain accumulated evidences which reported that BMSC could not withstand its characteristics for longer passages as they tend to increase its telomerase activity and undergo transformation (Pal et al 2008;Miura et al 2006). However, we found that only one sample reached P20 and the remaining samples could not be passaged beyond P15, thereby providing evidence that bone marrow can be extensively cultured without losing its potency until P15.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…On the other hand, our results were in contradictory to certain accumulated evidences which reported that BMSC could not withstand its characteristics for longer passages as they tend to increase its telomerase activity and undergo transformation (Pal et al 2008;Miura et al 2006). However, we found that only one sample reached P20 and the remaining samples could not be passaged beyond P15, thereby providing evidence that bone marrow can be extensively cultured without losing its potency until P15.…”
Section: Discussioncontrasting
confidence: 99%
“…Literary evidence reported that BMSC are not susceptible to malignant transformation and remain appropriate for therapeutic approaches (Bernardo et al 2007). However, there are reports suggesting loss of stem cell characteristics, increase in telomerase activity and malignant transformation under prolonged culturing of BMSC (Pal et al 2008;Miura et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…First of all, two studies noted that the post thaw viability measured varied with the timing of the assay/time post thaw. 30,32 Specifically, the viability of the MSCs declined with time post thaw, with frozenthawed MSCs showing a decrease in viability from >80% at 2 hours to <40% at 8 hours when maintained at 4°C. 16 This was presumably because of post thaw apoptosis but markers of apoptosis were not monitored.…”
Section: Hematopoietic Stem Cellsmentioning
confidence: 99%
“…30,31 In developing a solution more appropriate for clinical use, Pal, Hanwate and Totey used different parenteral solutions (e.g., saline solution, Plasmalyte A) supplemented with 5% human serum albumin (HSA) and 10% DMSO. 32 Moon and colleagues used a vitrification solution of 40% ethylene glycol (EG) + 18% Ficoll 70 + 0.3 M sucrose to preserve MSCs isolated from amnion. 33 Cryopreservation or post thaw wash solutions are sometimes supplemented with additives intended to modulate cell response to the stresses of freezing and thawing (e.g., apoptosis inhibitors to reduce cell losses associated with post thaw apoptosis [34][35][36][37] ).…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…a. Mesenchymal stem cells (MSC). No consensus has been reached as to the optimal cryopreservation protocol of MSC, but most of the published efforts were guided by cryopreservation approaches for HSCs (G. Liu et al, 2008;Thirumala, Gimble, & Devireddy, 2010;Thirumala, Goebel, & Erik J Woods, 2009; (Pal, Hanwate, & Totey, 2008). Protocols utilizing anti-apoptotic agents, such as ROCK-inhibitors, have shown promise in preclinical experiments (Heng, 2009).…”
Section: Cryopreservation Of Non-hematologic Stem Cellsmentioning
confidence: 99%